Resident Macrophages in Cystic Kidney Disease - Li, Zhang (Kidney360, 2020)
Interstitial inflammation is an important feature of cystic kidney disease. Renal macrophages are the most well-studied inflammatory cell in the kidney, and their involvement in cyst formation has been reported in different animal models and patients with cystic kidney disease. Originally, it was believed that renal macrophages were maintained from a constant supply of bone marrow–derived circulating monocytes, and could be recruited to the kidney in response to local inflammation. However, this idea has been challenged using fate-mapping methods, by showing that at least two distinct developmental origins of macrophages are present in the adult mouse kidney. The first type, infiltrating macrophages, are recruited from circulating monocytes and gradually develop macrophage properties on entering the kidney. The second, resident macrophages, predominantly originate from embryonic precursors, colonize the kidney during its development, and proliferate in situ to maintain their population throughout adulthood. Infiltrating and resident macrophages work together to maintain homeostasis and properly respond to pathologic conditions, such as AKI, cystic kidney disease, or infection. This review will briefly summarize current knowledge of resident macrophages in cystic kidney disease.